PENGENALAN CERITA MITOLOGI MAKASSAR: LEGENDA PENJAGA TAHTA KEMBAR MELALUI BUKU DIGITAL ILUSTRASI KYRAN - Shabiriani, Uzda Nabila; Retanubun, Immanuel Sean Keane (Narada : Jurnal Desain dan Seni, 2024)
Sulawesi Island is rich in myths, one of which is the legendary tale from Makassar City. This research underlines the Legend of the Twin Thrones, a story about Suri Pa'langi, a warrior chosen by the twin spirits of Gowa and Tallo to protect Makassar from the threat of a portal that releases monsters. The story seamlessly interweaves historical fragments of the Gowa-Tallo Kingdom and fantasy in order to construct an interesting plot that reflects Makassar's cultural unity. Further, it is intended that the development of the Digital Illustrated Book "Kyran" will introduce the mythology of Makassarese to the youth of Indonesia. This study applies a descriptive narrative method and exploratory approach in the concept of pipeline art, including character, setting, and illustration with themes of fantasy, adventure, and action. The illustrations are colored with Makassar's characteristic colors and feature dark visuals that add to the mythological atmosphere. The main characters are Isla Neith, Erland Ghafari, Sanna Devana, Tirza Keres, and Suri Pa'langi. A moon-shaped portal that appeared 20 years ago is the main villain, unleashing monsters and wreaking havoc. Kyran is a digital book that shows mythology in an exciting and relatable way for teenagers. The results showed that the story significantly improved the teenagers' knowledge of Nusantara mythology and could be considered as a new media for learning. This book can also popularize Indonesian mythology worldwide.